Islamic education and missionary work in the Gambia, Ghana and Sierra Leone during the twentieth century - Skinner, David E. (Bulletin on Islam and Christian-Muslim relations in Africa, 1983)
Entwicklung des islamischen Schulwesens unter besonderer Berücksichtigung der Probleme der Anpassung an die Anforderungen des staatlichen Bildungssystems